Artistic Concept in the Cognitive Perspective - Gasparyan, Seda; Sargsyan, Mariana; Melik-Karamyan, Astghik (Armenian Folia Anglistika, 2016)
The present article aims at studying the phenomenon of artistic concept by providing a detailed analysis of linguistic choices and patterns in the text with a systematic consideration of the mental processes and representations that are involved in the process of interpretation. The tools provided by the recent developments in cognitive approach are applied to enlarge the scope of studies in artistic concepts in general and also to highlight the major features that make the artistic concept distinct from the general cultural concepts. The practical study is based on alienation – one of the key concepts exploited in the contemporary literature.
Keywords: artistic concept; subjective-evaluative component; cognitive approach; container schema